Cover Image, Volume 11, Issue 10. (26th October 2017) - Tam, Joshua; Wang, Ying; Vuong, Linh N.; Fisher, Jeremy M.; Farinelli, William A.; Anderson, R. Rox
Abstract : The cover image, by Joshua Tam et al., is based on the Research Article Reconstitution of full‐thickness skin by microcolumn grafting, DOI:10.1002/term.2174 .